Technology News - No. 503 - Hazcom Helper Compliance Tool For MSHA Rule 30 CFR Part 47 (The National Institute for Occupational Safety and Health (NIOSH), 2003)
Develop tools that mine personnel can use to comply with 30 CFR,Part 47. Background The new MSHA rule, 30 CFR, Part 47 (also known as the HazCom rule), requires all mines to develop a written program to track hazardous chemicals at their sites. More specifically, the rule requires that mines list all chemicals and determine which are hazardous; develop a written Hazard Communication Program; label all containers used to store hazardous chemicals; obtain or develop Material Safety Data Sheets (MSDS) for all chemicals stored or produced; provide miners with training in working around hazardous chemicals; and make information about hazardous chemicals available to all workers. All mines with six or more employees must have complied with the new rule by September 23, 2002, and mines with five or fewer employees will have to be in compliance by March 21, 2003.